Morpho-anatomical Studies of Intertidal Bivalve Glauconome chinensis (Gray, 1828) from West Bengal-Odisha Coast, India - Maiti, Saheli; Islam, Sk Saruk; Mahato, Sumana; Samanta, Samaresh; Midya, Sujoy (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
West Bengal-Odisha coastal mangrove ecosystem represent a productive and dynamic ecosystem enriched with diversified habitat and niches. The intertidal bivalve Glauconome chinensis has been reported presently in the intertidal zone of Subarnarekha estuary of West Bengal-Odisha coast of Bay of Bengal. The studied bivalve characterised by unique morphological and microanatomical features. The present paper deals with morphological (shape and sizes of the shell, siphon, mantle, foot, adductor muscle, gill, digestive gland, reproductive system) and also microanatomical characteristics of different body tissues of the intertidal bivalve Glauconome chinensis.